2012
DOI: 10.7589/0090-3558-48.2.307
|View full text |Cite
|
Sign up to set email alerts
|

Hematology and Plasma Biochemistry Values for the Giant Garter Snake (Thamnophis Gigas) and Valley Garter Snake (Thamnophis Sirtalis Fitchi) in the Central Valley of California

Abstract: ABSTRACT:Hematology and plasma biochemistry parameters are useful in the assessment and management of threatened and endangered species. Although reference ranges are readily available for many mammalian species, reference ranges for snakes are lacking for most species. We determined hematology and plasma biochemistry reference ranges for giant garter snakes (Thamnophis gigas) and valley garter snakes (Thamnophis sirtalis fitchi) living in four management areas in the Central Valley of California. White blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Although previous studies have reported baseline biochemical, blood gas, and hematology values for other viperid and colubrid snakes, this is the first study to establish guidelines for the interpretation of these analytes in copperheads and ratsnakes. The hematological and plasma biochemical results for copperheads and ratsnakes reported in this study were consistent with previously published values for both viperid and colubrid snakes, with the exception of higher leukocyte counts in the copperheads [4,[32][33][34][35][36][37][38][39]. This difference may be attributed to many variables such as species, age, size, time of year, methodology, and instrumentation [4,34,40].…”
Section: Discussionsupporting
confidence: 90%
“…Although previous studies have reported baseline biochemical, blood gas, and hematology values for other viperid and colubrid snakes, this is the first study to establish guidelines for the interpretation of these analytes in copperheads and ratsnakes. The hematological and plasma biochemical results for copperheads and ratsnakes reported in this study were consistent with previously published values for both viperid and colubrid snakes, with the exception of higher leukocyte counts in the copperheads [4,[32][33][34][35][36][37][38][39]. This difference may be attributed to many variables such as species, age, size, time of year, methodology, and instrumentation [4,34,40].…”
Section: Discussionsupporting
confidence: 90%
“…Such a kind of approach can provide reliable data when dealing with pets or farm animals, which live in strictly controlled conditions that sensibly reduce all those sources of variation in leukocyte profile proper to natural conditions, such as habitat heterogeneity, climatic variability, food distribution, and competition with other species, just to name a few. The effect of these external factors on leukocyte profile in wild populations, however, cannot be disregarded, as they can be one of the main causes of variation among populations, all over the range of the species [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is a proof that the Gökçeada water system is under significant pressure in terms of faecal pollution. The haematological and plasma biochemistry values determined to evaluate the health status of reptiles are affected by many internal and external environmental factors such as season, metabolic activity, reproductive cycle, age, sex, habitat, photoperiod and climate (Hidalgo-Vila et al, 2007;Wack et al, 2012). In this study, the RBC count, Hb concentration and WBC count were determined to be lower in the Dardanos samples.…”
Section: Discussionmentioning
confidence: 71%